Transversal bleustein-gulayev (B.G.) surface waves on a piezoelectric ceramic - PAJEWSKI, Wincenty (Archives of Acoustics, 1977)
In this paper the results of investigations of piezoelectric ceramic of the type lead zirconate-titanate (PZT) used as a basis for acoustic-electric waves (B.G.) are presented.The inhomogeneous structure of the ceramic, which results from a particular technological process, was observed to influence the surface wave propagation. The ceramic structure, which causes velocity differences in the propagation velocity of an acoustic wave in the surface layers, can preclude the possibility of transversal surface wave propagation or can create more favourable conditions for its propagation depending on whether the volume wave velocity increases or decreases within the surface layers.Investigations were carried out with plate and interdigital transducers for the generation of waves on the ceramic.